1996
DOI: 10.1021/cm9603260
|View full text |Cite
|
Sign up to set email alerts
|

New Families of Photocurable Oligomeric Fluoromonomers for Use in Dental Composites

Abstract: Photopolymerizable methacrylate-based resins with moderate-to-high organofluorine contents may improve the hydrophobicity, durability, and toughness of composites used in aesthetic dental filling applications. A variety of multifunctional oligomeric fluorinated monomers were developed and evaluated with the goal of identifying polymer systems that combine high strength, low water sorption, and minimal polymerization shrinkage. Certain fluorooligomer resin compositions prepared here appear capable of successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…It is generally considered that polymerization of monomers with large molecular volume and low double bond content will result in the lower polymerization shrinkage [12,13] and polymerization of monomers with low viscosity will result in the higher double bond conversion [14][15][16][17]. It has been reported that the branchedpolymers have both a large molecular volume and low viscosity [18].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally considered that polymerization of monomers with large molecular volume and low double bond content will result in the lower polymerization shrinkage [12,13] and polymerization of monomers with low viscosity will result in the higher double bond conversion [14][15][16][17]. It has been reported that the branchedpolymers have both a large molecular volume and low viscosity [18].…”
Section: Introductionmentioning
confidence: 99%
“…Polymerization‐induced phase separation can also occur between reactive species. Fluorinated methacrylate monomers exhibit phase separation of growing polymer from unreacted monomer upon polymerization 41. The polymerization of a fluorinated acrylate produces a phase‐separated homopolymer when the fluorocarbon side chains selectively associate to minimize interactions with the hydrocarbon polymer backbone chains formed during polymerization 42.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, a visible light photoinitiator consisting of CQ and ethyl p-(N,N-dimethylamino)benzoate (EDMAB) as the tert-amine is used in commercial dental resin formulations. [4,[15][16][17] Upon exposure, CQ is transferred to a triplet excited state, which combines with the DMA group of EDMAB to form an exciplex. Then the resulting exciplex generates the reactive free radical at the a-carbon of a DMA group; this is considered to be the effective initiating species for the polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…There have been furious research efforts to modify the Bis-GMA type methacrylates by incorporating suitable functional groups. [1,[15][16][17][21][22][23] The authors have reported some unique results obtained with modified Bis-GMAs, which have additional methacrylate groups, to improve the water uptake and viscosity problems in light-curable dental polymers. [24,25] In this paper, we report a new type of polymerizable, aromatic tert-amines, similar to the modified Bis-GMAs, with EDMAB analogues for enhancing photosensitivity as well as improving compatibility.…”
Section: Introductionmentioning
confidence: 99%